Justiça restaurativa : uma opção na solução de conflitos envolvendo violência doméstica e familiar contra a mulher - Mesquita, Marcelo Rocha (2015)
This study aims to analyze the dissatisfaction of women victims of domestic and family violence with the strategy used by most of the feminist movement, evidenced in the Law|Maria da Penha|, to use the criminal law and its retributive model, as a tool anti-discrimination and gender-based violence, and to identify restorative justice as an alternative to supply better the expectations and needs of women. For this purpose, a field research in the Domestic and Family Violence against Women Court in Aracaju County (SE), which were heard 191 (one hundred and ninety-one) victims in criminal proceedings in that court from September to November 2013, confirming the dissatisfaction of women with the answer given by the traditional model and their desire of a discursive criminal justice, characteristic of restorative model. Initially, the issue of gender violence is approached, an issue that has gained greater importance in Brazil, especially from the 80´s with the work of feminist groups and, more recently, with the advent of Law No. 11.340/2006. After, indicate that the mentioned law made a clear option for retributive model of criminal justice, given an existing trend in several countries in Europe and Latin America, pointing the criticisms of this model in conflict resolution involving gender violence. Afterwards, foments the analysis and discussion of the data collected and the field research conducted and previously mentioned. Further mentioned. Further continues with an analysis of restorative justice as a new way of looking at crime and justice, relating this criminal justice model with the discursive theory developed by the German philosopher Jürgen Habermas, in addition to exposing the concept, objectives, principles and values, pointing also the main differences between the new and the traditional model. Follows pointing out objections and advantages of the use of restorative justice in conflict resolution involving domestic violence against women. Finally, points restorative justice as an option that should be made available to women victims of domestic violence, because It is a model of justice that serves more adequately to women´s concerns, while respecting their autonomy and dignity, also opening the prospect of real change of men and women behavior on issues involving gender violence.